2017
DOI: 10.1017/rep.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

The Race Project: Researching Race in the Social Sciences Researchers, Measures, and Scope of Studies

Abstract: While the concept and measurement of race has been a longstanding focus of social science research, capturing its significance requires a broader notion than utilizing only racial group categories. More recently, race has been treated as both a “characteristic” and a set of experiences that affect a multitude of life conditions and outcomes. This discussion and analysis moves away from treating race as only a categorical and static characteristic to a multi-dimensional concept that is dynamic, relational, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 90 publications
(98 reference statements)
0
28
0
Order By: Relevance
“…Treating racial/ethnic categories as immutable entities also contributes to the naturalization of racial/ethnic inequities in oral health. Sociological accounts of race/ethnicity clearly show that it has much more to do with broader processes, such as power and oppression, than with biologyeven though racial/ ethnic classification may be based on phenotypic characteristics (2,6,48,49). When oral health studies make no reference to the social dynamics that give rise to racial/ ethnic categories, they may reinforce views that not only take race/ethnicity as a biological essence of individuals, but also lend credence to the idea that humanity can be easily and neatly divided into discrete racial/ethnic categories.…”
Section: Recommendation #1: Fostering Anti-racism In Oral Health Resementioning
confidence: 99%
“…Treating racial/ethnic categories as immutable entities also contributes to the naturalization of racial/ethnic inequities in oral health. Sociological accounts of race/ethnicity clearly show that it has much more to do with broader processes, such as power and oppression, than with biologyeven though racial/ ethnic classification may be based on phenotypic characteristics (2,6,48,49). When oral health studies make no reference to the social dynamics that give rise to racial/ ethnic categories, they may reinforce views that not only take race/ethnicity as a biological essence of individuals, but also lend credence to the idea that humanity can be easily and neatly divided into discrete racial/ethnic categories.…”
Section: Recommendation #1: Fostering Anti-racism In Oral Health Resementioning
confidence: 99%
“…The Race, Ethnicity, and Politics (REP) subfield has long argued that race is central to understanding American politics and that it is critical that we conceptualize these issues intersectionally, both at the individual and institutional levels (Strolovitch 2007;Novkov 2009;Beltrán 2011;Frances 2015;Hancock 2016;Hanchard 2019;Lemi and Brown 2019). Conceptualizations of race as an object of study has advanced in important ways since the mid-20th century but more needs to be done (Garcia 2017). We need to think deeply about the intersection between white supremacy and democratic governance in the United States.…”
Section: Modern Sexismmentioning
confidence: 99%
“…In his effort to determine what should be included in studying race in the social sciences, Garcia found that recent studies were more sensitive to multiple race categories than those conducted in earlier time periods. 48 James described how scholars who study race specifically treat it as a more dynamic and fluid concept that helps explain social processes, while others who simply use the concept of race treat it as a more fixed characteristic used to differentiate between "populations" in their studies. 49 George Henderson argued there are no pure races, which makes defining people by race arbitrary.…”
Section: Identitymentioning
confidence: 99%